Constructing Defective Heterojunctions of BiOBr Nanosheets and Hollow NH2‐functionalized MOFs for Visible‐light‐driven CO2 Reduction with Nearly 100% CO Selectivity by Pure H2O. Issue 8 (24th February 2023) - Yang, Menghan; Han, Yali; Ding, Junfang; Guo, Yan; Han, Chenhui; Gu, Xiaojun
Abstract: To rationally design photocatalysts with high generation rate and selectivity of target product remains an ongoing challenge for CO2 conversion in pure H2 O. Herein, from the viewpoint of enhancing the separation efficiency of photoinduced electron‐hole pairs and the adsorption ability of CO2 molecule, we have constructed a series of Z‐scheme defective heterojunctions of BiOBr nanosheets and hollow NH2 ‐functionalized metal‐organic framework (MOF) MIL‐125 with Ti ions as metal centers (noted as NH2 ‐MIL‐125(Ti)). Systematic characterization demonstrates that the BiOBr nanosheets are anchored on the surface of hollow NH2 ‐MIL‐125(Ti), which facilitates the efficient visible‐light‐driven catalytic reduction of CO2 to CO with nearly 100% selectivity by pure H2 O. Especially, the CO generation rate of optimized catalyst with oxygen vacancies reaches 459.7 μmol g −1 h −1, which is higher than those of all the previously reported photocatalysts without sacrificial reagents. This approach provides a new insight for using inorganic semiconductors to fabricate semiconducting MOFs for high‐efficiency photocatalytic reduction CO2 into value‐added chemicals by pure H2 O. Abstract : BiOBr nanoplates were successfully attached to hollow NH2 ‐MIL‐125(Ti) surface to form Z‐format defect heterojunction. In pure water, the optimized oxygen‐containing vacancy catalyst reduced CO2 to CO with near 100% selective high‐efficiency visible light, and the rate of CO formation reached 459.7 μmol g −1 h −1, which is higher than that of all photocatalysts reported previously.